META-ANALISIS PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Lahma Ainun Sajidah; Mohammad Taufiq; Muhammad Thamrin; Sri Hartatik (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aims to determine the effect of the Make a Match learning model on learning outcomes of elementary school students. The method used in this research is meta-analysis method. This study is to determine whether the Make a Match learning model can improve student learning outcomes. In the next stage, collect relevant articles to collect data. The data was obtained from online journal searches through Google Scholar, where 10 articles were obtained. The keywords used are